Late Aptian (Cretaceous) climate changes in northeastern Brazil: A reconstruction based on indicator species analysis (IndVal) - Carvalho, Marcelo de Araujo; Bengtson, Peter (Palaeogeography, palaeoclimatology, palaeoecology, 2017)
The flora preserved in upper Aptian rocks of South America and Africa is typical of warm climate conditions and commonly associated with semi-arid to arid climate. Warmth-loving conifers of the family Cheirolepidiaceae and their pollen Classopollis are recorded in upper Aptian rocks in most of the South Atlantic margin basins. However, an increase in indicators of humid conditions (e.g., ferns) is recorded in most sedimentary basins of Brazil. The method of indicator species analysis (IndVal) was applied as a tool for reconstructing the vegetation during the late Aptian. The IndVal index expresses which taxa are strongly associated with particular groups of samples. The vegetation reflects climate changes, and the IndVal indices illustrate how the taxa interacted through time and reveal patterns in the changing composition of the vegetation. The material studied derives from two well sections drilled through the Riachuelo Formation in the Sergipe Basin, GTP-17-SE (Angico Member, 70 samples) and GTP-24-SE (Taquari Member, 108 samples). The indicator species are strongly associated with particular stratigraphic intervals. IndVal indices for the Angico section indicate seven taxa associated with four intervals, viz. Classopollis classoides (Interval AS-1); Callialasporites segmentatus and Cicatricosisporites avnimelechi (Interval AS-2); Verrucosisporites spp. and Cicatricosisporites microstriatus (Interval AS-3); Araucariacites australis and Cyathidites spp. (Interval AS-4). Values for the Taquari section indicate nine taxa associated with four intervals, viz. Classopollis classoides (Interval TS-1); Uesuguipollenites callosus, Callialasporites segmentatus Bennettitaepollenites regaliae, Cyathidites spp., Cicatricosisporites spp. and Araucariacites australis (Interval TS-2); Retitriletes spp. (Interval TS-3); Araucariacites australis and Verrucosisporites spp. (Interval TS-4). Two phases, dry and wet, are recognized in both sections. The dry phase is characterized by high to very high abundance of Classopollis classoides. A conspicuous change in vegetation is recorded, with an increase in ferns and upland flora, in particular Araucariacites australis. A. australis is the second most abundant terrestrial palynomorph. In the late Aptian of South America and Africa Araucariacites is generally associated with an upland flora and warm and humid climates, which may explain its association with fern spores. The replacement of Classopollis by Araucariacites and ferns reflects a change from a dry to wet phase. The change in flora may be the result of dislocation of the Intertropical Convergence Zone (ITCZ) and a relative sea-level rise.
Gesehen am 30.04.2018